Higher reticulocyte counts are associated with higher mortality rates in hemodialysis patients: a retrospective single-center cohort study. Issue 1 (December 2017) - Takagi, Chieko; Ono, Kumeo; Matsuo, Hidenori; Nagano, Nobuo; Nojima, Yoshihisa
Abstract Background We assessed laboratory data related to mortality in hemodialysis (HD) patients. In our preliminary study, we examined all of the data for HD outpatients in our facility according to whether the patient had survived. A statistically significant difference was observed for the reticulocyte count, which has not previously been considered a prognostic factor. We subsequently verified the relationship between all-cause and cardiovascular mortality and reticulocyte count. Methods We retrospectively analyzed the data of 358 hemodialysis outpatients who were followed up for an average of 41.4 months. The patients were divided into quartiles according to the reticulocyte count levels. Results Higher reticulocyte counts were associated with female gender, an increase in interdialytic body weight gain, serum erythropoietin level, white blood cell count, and increased levels of lactate dehydrogenase, inorganic phosphorus, non-high-density lipoprotein, and glucose. As compared with patients in the lowest quartile, those in the highest quartile showed significantly higher adjusted hazard ratios (HRs) for all-cause (HR 3.12; 95% confidence interval (CI) 1.26 to 7.74) and cardiovascular (HR 4.93; 95% CI 1.24 to 19.56) mortality. For every 104 cells/μL increment in the reticulocyte count, the adjusted HRs for all-cause and cardiovascular mortality were 1.33 (95% CI 1.17 to 1.51) and 1.38 (95% CI 1.17 to 1.63), respectively. The association of reticulocyte count with all-cause and cardiovascular mortality was independent of other prognostic factors. Stepwise multivariable Cox analysis indicated that only age showed stronger association with all-cause mortality than reticulocyte count. Regarding cardiovascular mortality, reticulocyte count was found as the strongest progenitor. We also examined the relationship between the reticulocyte count and the temporal hemoglobin trend (a slope of changes in hemoglobin levels over time). A statistically significant negative correlation was found. Conclusions Higher reticulocyte counts were associated with higher mortality. We speculate that this result reflects tissue hypoxia, which results in a higher erythropoietin level, or a compensatory erythropoietic response due to the accelerated clearance of erythrocytes. Prospective studies are warranted to confirm our findings.